Annual Plan 1984-85 Government of India Planning Commission - Planning Commission (Planning Commission, 1984)
The Annual Plan 1984-85 which marks the final year of the Sixth Plan, represents a continuing process in terms of objectives socio-economic policies, investments and benefit targets as visualised in the Sixth Plan. Inevitably it reflects important adaptations arising out of me changing conditions, performance of the economy over the first four years of the Plan as also the fresh developments arising in different sectors of the economy.
Government of India, Planning Commission